Cartilage repair scaffold and preparation method thereof
By designing a cartilage repair stent including lubricating layer, surface layer and bonding layer, the problem of the inability to simultaneously repair cartilage damage and reconstruct lubrication function in the prior art is solved, and the long-term lubrication effect of the stent is achieved, and the repair and protection of cartilage is promoted.
Patent Information
- Application Number
- CN201910554769.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2039-06-25
AI Technical Summary
The existing cartilage repair stent cannot simultaneously repair cartilage damage and reconstruct cartilage lubrication function, and the lubrication effect cannot be maintained for a long time.
A scaffold including a lubricating layer, a surface layer and a bonding layer was designed. The lubricating layer was made of non-degradable material, and the surface layer had a porous structure, and was made of biocompatible degradable or biostable non-degradable material. The bonding layer connects the lubricating layer and the surface layer to form a fastening structure to ensure the long-term lubricating function of the lubricating layer.
The stent can provide long-term lubrication at the implanted joint, promote cartilage repair and reconstruction, reduce cartilage wear after repair, and protect joint health.
Smart Images

Figure CN112120834B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical equipment, and in particular to a scaffold for cartilage repair and a preparation method thereof. Background Art
[0002] Articular cartilage lesions are a common clinical disease. The main causes include cartilage degeneration and lesions caused by trauma, inflammation, and joint activity pressure. Once the lesions occur, the damage continues to accumulate and eventually causes joint diseases. In severe cases, it can lead to osteoarthritis, also known as degenerative arthritis, which is a type of arthritis that damages the articular cartilage or subarticular bones. It mainly occurs in middle-aged and elderly people, and is also common in people who are overweight, have different leg lengths, or whose joints are under high pressure for a long time due to work. In recent years, with the prevalence of exercise, osteoarthritis has gradually become younger. Its common symptoms are joint pain or stiffness, and in severe cases it can cause weakness or numbness in the limbs, which greatly affects daily life and work. It has become one of the important research and development topics in the world.
[0003] Cartilage has a porous structure and lacks blood vessels, nerves and undifferentiated cells. Therefore, its self-repair ability is limited and it is basically unable to self-repair after wear and tear. At present, the traditional clinical surgical methods for treating articular cartilage lesions mainly include bone marrow stimulation, cartilage inlay and artificial joint replacement. However, these surgical methods generally have problems such as easy recurrence and repeated disease.
[0004] In recent years, chondrocyte transplantation, microfracture technology, artificial cartilage and tissue-engineered cartilage repair technology have developed rapidly, which have better effects on the treatment of articular cartilage lesions. Stents are required in the process of using the above technologies. Existing stents do not have the function of simultaneously repairing cartilage damage and rebuilding the lubrication function of cartilage.
[0005] For example, Chinese patent document CN 108159496 A discloses a dual-factor program-released biomimetic oriented cartilage scaffold, including a surface layer made of collagen, chitosan, hyaluronic acid, and PLGA microspheres loaded with KGN, and a transitional layer made of collagen, chitosan, and PLL-HS nanoparticles loaded with TGF-β1, and then the two are bonded with silk fibroin as an adhesive to obtain a biomimetic oriented cartilage scaffold with an upper and lower double-layer structure. The main function of this scaffold is to repair osteoarthritis cartilage defects. Although the hyaluronic acid therein has a lubricating effect, hyaluronic acid is a degradable material and will gradually degrade after use, losing its lubricating function, and does not have the function of maintaining the lubricating function of cartilage for a long time. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art cartilage repair scaffold that it does not have the function of simultaneously repairing cartilage damage and rebuilding the lubrication function of cartilage, and that its lubrication function can be maintained for a long time, thereby providing a cartilage repair scaffold and a preparation method thereof.
[0007] In order to solve the above technical problems, on the one hand, the present invention provides a scaffold for cartilage repair, comprising:
[0008] The lubricating layer is made of non-degradable material and has a lubricating effect;
[0009] The surface layer comprises a porous layer having a porous structure, wherein the surface layer is made of a biocompatible and degradable material; or, the surface layer is made of a biostable and non-degradable material;
[0010] The bonding layer is connected between the lubricating layer and the porous layer, so that the lubricating layer forms a fastening structure with the porous layer through the bonding layer.
[0011] Optionally, the surface layer further includes a barrier layer, the porous layer includes a first porous layer, and the barrier layer is connected between the first porous layer and the bonding layer to isolate the first porous layer from the bonding layer.
[0012] Optionally, the porous layer further includes a second porous layer, and the second porous layer is connected between the barrier layer and the bonding layer.
[0013] Optionally, the ratios of the thickness of the surface layer, the thickness of the bonding layer and the thickness of the lubricating layer to the total thickness of the stent are 60%-80%, 0.1%-10% and 1%-35%, respectively.
[0014] Optionally, the friction coefficient of the non-degradable material used to prepare the lubricating layer is 0.05-1.
[0015] Optionally, the friction coefficient of the non-degradable material used to prepare the lubricating layer is 0.05-0.3.
[0016] Optionally, the lubricating layer is made of the following materials: one or more of polymer oil gel or porous materials containing lubricating liquid.
[0017] Optionally, the porous material containing the lubricating liquid has a pore size of 0.1-1 μm and a porosity of 25%-95%, and the mass fraction of the lubricating liquid in the porous material is 20%-80%.
[0018] Optionally, the viscosity of the lubricating liquid is 5-10000 cst.
[0019] Optionally, the surface layer is made of a 3D printable biomedical polymer material.
[0020] Optionally, the pore diameter of the porous layer is 10-500 μm.
[0021] Optionally, the porosity of the porous layer made of degradable material is 20%-90%, and the porosity of the porous layer made of non-degradable material is not less than 90%.
[0022] Optionally, the porous structure is a regular through hole with uniform size; or,
[0023] The porous structure is a sponge structure.
[0024] Optionally, the bonding layer is made of the following materials: one or more of polymer oil gel, porous material containing lubricating liquid, 3D printable biomedical polymer material or bioadhesive.
[0025] Optionally, the polymer oil gel is polydimethylsiloxane oil gel;
[0026] The porous material containing lubricating liquid is a polytetrafluoroethylene porous membrane containing perfluorinated lubricating oil;
[0027] The 3D printable biomedical polymer material is one or more of polylactic acid, polycaprolactone, polyvinyl alcohol or thermoplastic polyurethane;
[0028] The biological adhesive is α-butyl cyanoacrylate.
[0029] Optionally, the Young's modulus of the bracket is 1-100 MPa, and the compressive strength is not less than 1 MPa.
[0030] In another aspect, the present invention provides a method for preparing a cartilage repair scaffold, comprising the following steps:
[0031] Forming a biocompatible degradable material into a porous layer by 3D printing; or forming a biostable non-degradable material into a porous layer by 3D printing;
[0032] The non-degradable material having lubricating effect is made into a lubricating layer;
[0033] The bonding layer is disposed between the porous layer and the lubricating layer to form a bracket.
[0034] In another aspect, the present invention provides a method for preparing a cartilage repair scaffold, comprising the following steps:
[0035] The biocompatible degradable material is formed into a porous layer and a barrier layer by 3D printing; or the biostable non-degradable material is formed into a porous layer and a barrier layer by 3D printing;
[0036] The non-degradable material having lubricating effect is made into a lubricating layer substrate;
[0037] The bonding layer is arranged between the barrier layer and the lubricating layer substrate to form a preliminary sample of the bracket, and the lubricating layer substrate is subjected to lubricity treatment and then formed into the bracket.
[0038] Optionally, the method for performing lubricity treatment on the lubricating layer substrate comprises:
[0039] Swelling lubricating liquid: placing the lubricating layer substrate in the lubricating liquid to swell the lubricating layer substrate to swelling equilibrium; or,
[0040] Infusing lubricating liquid: Infusing lubricating liquid into the lubricating layer substrate, allowing it to stand, vacuum degassing, and solidifying to form.
[0041] Optionally, the 3D printing method includes: one or more of a fused deposition method, a selective laser sintering method or a laser photocuring method.
[0042] Optionally, the method for preparing the bonding layer includes: physically interlocking the surface layer and the lubricating layer or the lubricating layer substrate to form a bonding layer; or, bonding and curing the surface layer and the lubricating layer or the lubricating layer substrate with a bioadhesive to form a bonding layer.
[0043] Optionally, the method further includes performing surface pretreatment on the materials for preparing the lubricating layer, the bonding layer and the surface layer respectively.
[0044] The technical solution of the present invention has the following advantages:
[0045] 1. The stent provided by the present invention comprises a lubricating layer, a surface layer and a bonding layer, wherein the surface layer comprises a porous layer having a porous structure, and the bonding layer is connected between the lubricating layer and the porous layer, so that the surface layer can form a fastening structure with the lubricating layer through the bonding layer; after the stent is implanted in the joint, the porous layer having a porous structure in the surface layer can temporarily replace the natural cartilage, provide growth space for bone cells, blood vessels, nerves and chondrocytes, and provide transmission channels for oxygen, nutrients and metabolites, and at the same time can provide support for the new tissue at the joint, match the mechanical properties of the natural cartilage at the implantation site (joint), so that the new tissue can grow well; for patients with good cell proliferation ability, the surface layer is made of a biocompatible degradable material, and as the cells proliferate, the degradable material will slowly degrade and eventually be completely replaced by chondrocytes; for patients with limited cell proliferation ability, the surface layer is made of a non-degradable material with biological stability, and the surface layer has good biological stability, that is, the surface layer has good resistance to biological aging at the joint, providing sufficient proliferation time for the cells, so that the cartilage is gradually repaired.
[0046] The lubricating layer is made of a non-degradable material that has a lubricating effect on cartilage, so that the lubricating layer can maintain the lubricity of the joint for a long time, that is, the lubricating layer is equivalent to simulating the lubricating structure of cartilage, so that the scaffold can have a long-term lubricating effect, thereby ensuring that the repaired cartilage has a long-term lubricating function, reducing the wear of the repaired cartilage and protecting the health of the joint. Furthermore, the surface layer and the lubricating layer are combined together by the bonding layer, so that the scaffold has the function of repairing cartilage damage, and at the same time has the function of rebuilding the lubricating function of cartilage, and can maintain its lubricating function for a long time.
[0047] 2. The surface layer of the stent provided by the present invention also includes a barrier layer. When the lubricating layer contains liquid, the barrier layer can prevent the liquid in the lubricating layer from entering the first porous layer, ensuring that cells can adhere to the porous structure of the first porous layer, which is beneficial to cell reproduction.
[0048] 3. The ratio of the thickness of the surface layer to the total thickness of the scaffold provided by the present invention is 60%-80%, the ratio of the thickness of the bonding layer to the total thickness of the scaffold is 0.1%-10%, and the ratio of the thickness of the lubricating layer to the total thickness of the scaffold is 1%-35%. In this way, a stable scaffold structure can be formed to provide a stable growth space for cells.
[0049] 4. In the stent provided by the present invention, the lubricating layer is made of polymer oil gel or a porous material containing a lubricating liquid. When the lubricating layer is made of polymer oil gel, there is no need to inject liquid during the preparation of the lubricating layer, and the surface layer may have only a porous layer, or the surface layer has a porous layer and a barrier layer. When the lubricating layer is made of a porous material containing a lubricating liquid, there is a need to inject liquid during the preparation of the lubricating layer, and the surface layer is a porous layer and a barrier layer.
[0050] 5. The stent provided by the present invention has a porous material containing a lubricating liquid with a pore size of 0.1-1 μm and a porosity of 25%-95%, which can provide a suitable accommodation space for the lubricating liquid and is conducive to cell reproduction; the mass fraction of the lubricating liquid contained in the porous material is 20%-80%, which can ensure the lubricating effect of the lubricating layer and make the lubricating effect of the lubricating layer better.
[0051] 6. The friction coefficient of the non-degradable material used to prepare the lubricating layer of the scaffold provided by the present invention is 0.05-0.3, so that the lubricating layer has a better lubricating effect on the cartilage. The lower the friction coefficient, the better the lubricating effect of the lubricating layer on the cartilage.
[0052] 7. The stent provided by the present invention has a lubricating liquid with a viscosity of 5-10000 cst. The viscosity range of the lubricating liquid is wide, and a lubricating liquid with an appropriate viscosity can be selected according to the properties of the lubricating layer material to ensure that the lubricating liquid exists stably after entering the lubricating layer material, has a low friction coefficient, and does not significantly reduce the mechanical properties of the lubricating layer.
[0053] 8. The surface layer of the stent provided by the present invention is made of a 3D printable biomedical polymer material, so that the surface layer can be made by 3D printing. The 3D printing method is simple and convenient to operate. A 3D model can be designed according to the needs of the lesion site (joint), and a stent of a specific shape can be printed to improve the matching degree between the stent and the joint, thereby creating a space more suitable for cell growth.
[0054] 9. The pore diameter of the porous layer of the scaffold provided by the present invention is 10-500 μm, which is beneficial to improving the mechanical properties of the porous layer, enhancing the cell reproduction environment, and being more conducive to cell growth.
[0055] 10. The scaffold provided by the present invention has a porous layer made of degradable materials with a porosity of 20%-90%. Because the degradable materials will eventually degrade, the porous layer has relatively less space for cell growth. The porous layer made of non-degradable materials has a porosity of not less than 90%. Because the non-degradable materials will not be degraded eventually, sufficient growth space needs to be provided for cell reproduction to form a stable cartilage structure.
[0056] 11. The scaffold provided by the present invention has a porous structure with regular through holes of uniform size. Regular through holes have better mechanical properties and better support, making the spatial structure for chondrocyte growth more stable. The porous structure is a sponge structure with both macropores and micropores, which makes the adsorption performance of chondrocytes in the porous structure better and can promote the growth of chondrocytes.
[0057] 12. In the stent provided by the present invention, the bonding layer is made of one or more materials selected from the group consisting of polymer oil gel, porous material containing lubricating liquid, 3D printable biomedical polymer material or bioadhesive, so that the connection performance between the bonding layer and the lubricating layer and the surface layer can be improved, so that the surface layer, the bonding layer and the lubricating layer can be more firmly connected.
[0058] 13. The surface layer of the stent provided by the present invention is supported by one or more of polylactic acid, polycaprolactone, polyvinyl alcohol or thermoplastic polyurethane. The degradation rate of polylactic acid and polycaprolactone and the rate of mechanical property decline caused by degradation are adapted to the rate of cartilage tissue regeneration, so that the surface layer of the stent remains effective during use (service process).
[0059] 14. The scaffold provided by the present invention has a Young's modulus of 1-100Mpa and a compressive strength of not less than 1Mpa, which can make the scaffold have a better supporting effect and better match the mechanical properties of the natural cartilage at the implantation site (joint), which is more conducive to cell growth.
[0060] 15. The preparation method of the scaffold provided by the present invention is to form a porous layer by 3D printing a biocompatible degradable material, or to form a porous layer by 3D printing a non-degradable material with biological stability, to provide a space for the growth and proliferation of chondrocytes, so that the porous layer has the function of repairing cartilage. At the same time, the 3D printing molding method is simple and convenient to operate. A 3D model can be designed according to the needs of the lesion site (joint), and a porous layer of a specific shape can be printed to improve the matching degree between the porous layer and the joint, and to build a space more suitable for the growth of chondrocytes. The non-degradable material with lubricating effect is made into a lubricating layer, so that the lubricating layer has a long-term lubricating effect, which can keep the joint in a lubricated state for a long time. The lubricating layer and the porous layer are fixed by a bonding layer to form a stable scaffold structure, so that the scaffold can better adapt to the environment of the joint. At the same time, the scaffold has the function of repairing cartilage and rebuilding the lubricating function of cartilage, and can maintain its lubricating function for a long time.
[0061] 16. The preparation method of the scaffold provided by the present invention forms a porous layer and a barrier layer from a biocompatible degradable material through 3D printing, or forms a porous layer and a barrier layer from a biostable non-degradable material through 3D printing, so that the porous layer has the function of repairing cartilage. At the same time, the 3D printing method is simple and convenient to operate. A 3D model can be designed according to the requirements of the lesion site (joint), and a porous layer of a specific shape can be printed to improve the matching degree between the porous layer and the joint, thereby constructing a space more suitable for the growth of chondrocytes.
[0062] A non-degradable material with lubricating effect is made into a lubricating layer substrate, the surface layer and the lubricating layer are fixed by a bonding layer, and the bonding layer is arranged between the barrier layer and the lubricating layer to prevent the lubricating liquid of the lubricating layer from flowing to the porous layer through the bonding layer when the lubricating layer is subjected to lubricity treatment, thereby ensuring that cells can adhere to the porous structure, which is beneficial to cell reproduction; after the lubricating layer substrate is subjected to lubricity treatment, the lubricating layer has a long-term lubricating effect, which can keep the joint in a lubricated state for a long time, that is, the scaffold has the function of repairing cartilage and rebuilding the lubrication function of cartilage, and can maintain its lubrication function for a long time.
[0063] 17. The preparation method of the stent provided by the present invention forms a bonding layer by physically interlocking the surface layer and the lubricating layer or the lubricating layer substrate, so that the bonding layer is formed simultaneously in the process of preparing the surface layer and the lubricating layer or the lubricating layer substrate, which reduces the preparation time of the stent and simplifies the preparation steps of the stent. The surface layer and the lubricating layer or the lubricating layer substrate are bonded and solidified by a biological adhesive to form a bonding layer, so that the stent can be made of the ready-made surface layer and lubricating layer or the lubricating layer substrate, and the surface layer, the lubricating layer or the lubricating layer substrate can be purchased externally or prepared by oneself, which improves its selectivity and makes the preparation of the stent more convenient and quick.
[0064] 18. The method for preparing the stent provided by the present invention comprises performing surface pretreatment on the materials for preparing the lubricating layer, the bonding layer and the surface layer, so that a good connection can be formed between the bonding layer and the lubricating layer and the surface layer, thereby forming a stable stent. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0066] Figure 1 This is the first implementation structure of the bracket provided in the specific implementation mode of the present invention;
[0067] Figure 2 This is the second implementation structure of the bracket provided in the specific implementation mode of the present invention;
[0068] Figure 3 This is the third implementation structure of the bracket provided in the specific implementation mode of the present invention.
[0069] Reference numerals:
[0070] 1. Lubricating layer; 2. Bonding layer; 3. Surface layer; 31. First porous layer; 32. Second porous layer; 33. Barrier layer. DETAILED DESCRIPTION
[0071] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0072] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0073] A scaffold for cartilage repair comprises a lubricating layer 1, a bonding layer 2 and a surface layer 3, wherein the surface layer 3 comprises a porous layer with a porous structure and a barrier layer 33, wherein the barrier layer 33 is a solid structure, and when the porous layer comprises a first porous layer 31, the barrier layer 33 is connected between the first porous layer 31 and the bonding layer 2, and the barrier layer 33 is used to isolate the first porous layer 31 and the bonding layer 2, and when the porous layer comprises a first porous layer 31 and a second porous layer 32, the barrier layer 33 is connected between the first porous layer 31 and the second porous layer 32, and the second porous layer 32 is connected between the barrier layer 33 and the bonding layer 2, and the barrier layer 33 is used to isolate the barrier layer 33 from the first porous layer 31.
[0074] The ratio of the thickness of the surface layer 3 to the total thickness of the stent is 60%-80%. It can be understood that when the surface layer 3 only includes the porous layer, it means that the ratio of the thickness of the porous layer to the total thickness of the stent is 60%-80%; when the surface layer 3 includes the porous layer and the barrier layer 33, it means that the ratio of the total thickness of the porous layer and the barrier layer 33 to the total thickness of the stent is 60%-80%. The ratio of the thickness of the bonding layer 2 to the total thickness of the stent is 0.1%-10%, and the ratio of the thickness of the lubricating layer 1 to the total thickness of the stent is 1%-35%.
[0075] The lubricating layer 1 is made of a non-degradable material with a friction coefficient of 0.05-1, so that the lubricating layer 1 has a good lubricating effect and can maintain its lubricating function for a long time.
[0076] The lubricating layer 1 is made of a non-degradable material with a friction coefficient of 0.05-0.3, which is one or more of a polymer oil gel or a porous material containing a lubricating liquid. The polymer oil gel is polydimethylsiloxane (PDMS) oil gel, or other non-degradable polymer oil gel with lubricating effect.
[0077] The porous material containing the lubricating liquid has a pore size of 0.1-1 μm, a porosity of 25%-95%, and a mass fraction of the lubricating liquid in the porous material of 20%-80%. The lubricating liquid is a liquid with low volatility and low surface energy, so that the lubricating liquid is not easy to volatilize and has a good lubricating effect. The viscosity of the lubricating liquid is 5-10000 cst. The porous material containing the lubricating liquid can be a polytetrafluoroethylene (PTFE) porous membrane containing perfluorinated lubricating oil, or other porous materials containing lubricating liquid that meet the above requirements.
[0078] The surface layer 3 is made of 3D printable biomedical polymer materials. The 3D printable biomedical polymer materials are: one or more of polylactic acid (PLA), polycaprolactone (PCL), polyvinyl alcohol (PVA) or thermoplastic polyurethane (TPU). These materials have better biocompatibility or biostability and are conducive to cell growth.
[0079] It is understandable that polyvinyl alcohol (PVA) includes degradable polyvinyl alcohol (PVA) and non-degradable polyvinyl alcohol (PVA); thermoplastic polyurethane (TPU) includes degradable thermoplastic polyurethane (TPU) and non-degradable thermoplastic polyurethane (TPU).
[0080] The pore diameter of the porous layer is 10-500 μm, and the porous structure of the porous layer is a regular through hole with uniform size; or the porous structure of the porous layer is a sponge structure with both macropores and micropores. It is understood that the macropores and micropores here are not used to limit the range of pore diameters, but only to illustrate that the porous structure is a sponge structure composed of pores of various pore diameters. The porosity of the porous layer made of degradable materials is 20%-90%, and the porosity of the porous layer made of non-degradable materials is not less than 90%.
[0081] Adding biocompatible active functional groups or active molecules containing the above active functional groups to the surface of the material for preparing the surface layer 3 can increase the activity of cells and facilitate cell adhesion, growth and proliferation. The active functional groups can be one or more of hydroxyl, carboxyl and amino groups. The active molecules containing the above active functional groups can be one or more of chitosan, amino acids, small molecule polypeptides or proteins.
[0082] The barrier layer 33 is made of one or more of polymer oil gel, porous material containing lubricating liquid, 3D printable biomedical polymer material or biological adhesive. The biological adhesive can be α-butyl cyanoacrylate or other preparations with biological adhesive effect.
[0083] The Young's modulus of the bracket is 1-100Mpa, and the compressive strength is not less than 1Mpa.
[0084] A method for preparing a scaffold for cartilage repair, comprising introducing active functional groups or active molecules containing the above-mentioned active functional groups on the surface of a biomedical polymer material that can be used for 3D printing, and then pretreating the surface of the material for preparing a surface layer 3, a lubricating layer 1 and a bonding layer 2. The pretreatment method includes surface treatment or chemical modification, etc. The surface treatment method includes: surface oxygen plasma treatment, high-intensity ultraviolet irradiation or high-energy ray irradiation, etc. The chemical modification method includes: surface grafting, surface oxidation or surface dip coating, etc.
[0085] Then, the biomedical polymer material is made into a surface layer 3 by a method of fused deposition method (FDM), selective laser sintering method (SLS) or laser photocuring method (SLA). The surface layer 3 can be only a porous layer, or a porous layer and a barrier layer 33. When the surface layer 3 has a barrier layer 33, the porous layer includes a first porous layer 31, the barrier layer 33 is connected between the first porous layer 31 and the bonding layer 2, and the barrier layer 33 is used to isolate the first porous layer 31 and the bonding layer 2; or, the porous layer includes a first porous layer 31 and a second porous layer 32, the barrier layer 33 is connected between the first porous layer 31 and the second porous layer 32, the second porous layer 32 is connected between the barrier layer 33 and the bonding layer 2, and the barrier layer 33 is used to isolate the barrier layer 33 from the first porous layer 31.
[0086] When the surface layer 3 has only a porous layer, the polymer oil gel can be made into the lubricating layer 1, and then the porous layer and the lubricating layer 1 are fixed and formed into a bracket by one of the polymer oil gel, 3D printable biomedical polymer materials or biological adhesives.
[0087] When the surface layer 3 is a porous layer and a barrier layer 33, the lubricating layer 1 can be made of a polymer oil gel, and then the porous layer and the lubricating layer 1 are fixed and formed into a bracket by one or more of a polymer oil gel, a 3D printable biomedical polymer material or a bioadhesive. Alternatively, the porous material is made into a lubricating layer 1 substrate, and then the porous layer and the lubricating layer 1 substrate are fixed and formed by one or more of a polymer oil gel, a 3D printable biomedical polymer material or a bioadhesive, and finally the lubricating layer 1 substrate is placed in a beaker containing a lubricating liquid until the lubricating layer 1 substrate is swollen and balanced to form a bracket.
[0088] As an alternative embodiment, the lubricating liquid can be poured into the lubricating layer 1 substrate and then left to stand to form a bracket. The corresponding treatment method for lubricity treatment of the lubricating layer 1 substrate varies according to the material used to prepare the lubricating layer 1 substrate. For example, when the lubricating layer 1 is made of an oil gel type material, the lubricating layer 1 substrate is placed in a beaker containing the lubricating liquid until the lubricating layer 1 substrate is swollen and balanced; when the lubricating layer 1 is made of a porous membrane type material, the lubricating liquid is poured into the lubricating layer 1 substrate and then left to stand.
[0089] The oil gel type material here refers to the material before the oil is absorbed by the material for preparing the oil gel. For example, the oil gel type material is PDMS. The porous membrane type material is a porous membrane that has not been perfused with lubricating liquid. For example, the porous membrane type material can be a PTFE porous membrane.
[0090] The preparation method of the bonding layer 2 includes: forming the bonding layer 2 by physically interlocking the surface layer 3 and the lubricating layer 1 or the base material of the lubricating layer 1; or, bonding and curing the surface layer 3 and the lubricating layer 1 or the base material of the lubricating layer 1 by a biological adhesive to form the bonding layer 2; or, coating one or more of polylactic acid, polycaprolactone, polyvinyl alcohol or thermoplastic polyurethane between the surface layer 3 and the lubricating layer 1 or the base material of the lubricating layer 1 after melting and curing to form the bonding layer 2. In this case, one or more of polylactic acid, polycaprolactone, polyvinyl alcohol or thermoplastic polyurethane after melting is equivalent to having the function of an adhesive.
[0091] Example 1
[0092] PCL-PDMS composite scaffold (PCL is degradable)
[0093] Put PCL on the sample stage of the 3D printer, adjust the base plate temperature to 30°C, the nozzle temperature to 200°C, and print the first porous layer and the barrier layer with a total thickness of 6.5 mm, wherein the thickness of the barrier layer is 0.2 mm, the pore size in the first porous layer is 10 μm, and the porosity is 89%;
[0094] Dow Corning 184A component and Dow Corning 184B component were mixed in a mass ratio of (10:1), stirred evenly to form a PDMS precursor, poured into a mold with a thickness of 1 mm, allowed to stand for 10 min, and vacuum degassed until there was no foam in the PDMS precursor. The mold and the PDMS precursor were placed in an oven at 50°C for curing for 1 h to obtain a nearly completely cured PDMS lubricating layer substrate.
[0095] Continue to pour 1mm thick PDMS precursor into the mold, let it stand for 10 minutes, and vacuum degassing until there is no foam in the PDMS precursor to form a bonding layer. Immerse the barrier layer in the bonding layer and cure it in an oven at 50°C to form a preliminary sample of the bracket;
[0096] Pour silicone oil with a viscosity of 10 cst into a beaker, immerse the PDMS lubricating layer substrate of the initial sample of the bracket in the silicone oil, and after the PDMS lubricating layer substrate has swollen to equilibrium, take out the initial sample of the bracket and let it stand for 30 minutes. Wipe off the excess silicone oil on the PDMS lubricating layer substrate to obtain the PCL-PDMS composite bracket.
[0097] Example 2
[0098] PLA-PDMS composite scaffold (PLA is degradable)
[0099] Put PLA on the sample stage of the 3D printer, adjust the bottom plate temperature to 60°C, the nozzle temperature to 200°C, and print the first porous layer, the barrier layer and the second porous layer with a total thickness of 6.0 mm, wherein the thickness of the barrier layer is 0.3 mm, the thickness of the second porous layer is 1.2 mm, the pore size in the first porous layer is 500 μm, the porosity is 75%, and the pore size in the second porous layer is 400 μm, and the porosity is 75%;
[0100] Dow Corning 184A component and B component were mixed in a mass ratio of (10:1), stirred evenly to form a PDMS precursor, poured into a mold with a thickness of 1 mm, left to stand for 10 min, and vacuum-degassed until there was no foam in the PDMS precursor. The mold and the PDMS precursor were then placed in an oven at 60°C for curing for 1 h to obtain a nearly completely cured PDMS lubricating layer substrate.
[0101] 0.03 mm α-butyl cyanoacrylate is coated on the second porous layer, and the PDMS lubricating layer substrate is adhered to the α-butyl cyanoacrylate, and cured to form a stent prototype;
[0102] Pour silicone oil with a viscosity of 10000 cst into a beaker, immerse the PDMS lubricating layer substrate of the initial sample of the bracket in the silicone oil, and after the PDMS lubricating layer substrate has swollen to equilibrium, take out the initial sample of the bracket and let it stand for 45 minutes. After wiping off the excess silicone oil on the PDMS lubricating layer substrate, a PLA-PDMS composite bracket is obtained.
[0103] Example 3
[0104] TPU-PDMS composite scaffold (TPU is non-degradable)
[0105] Place the TPU on the sample stage of the 3D printer, adjust the base plate temperature to 60°C, the nozzle temperature to 200°C, and print the first porous layer and the barrier layer with a total thickness of 6.0 mm, wherein the thickness of the barrier layer is 0.1 mm, the pore size in the first porous layer is 100 μm, and the porosity is 90%;
[0106] Dow Corning 184A component and Dow Corning 184B component were mixed in a mass ratio of (10:1), stirred evenly to form a PDMS precursor, poured into a mold with a thickness of 1 mm, left to stand for 10 min, and vacuum-degassed until there was no foam in the PDMS precursor. The mold and the PDMS precursor were placed in an oven at 60°C for curing for 1 h to obtain a nearly completely cured PDMS lubricating layer substrate.
[0107] Continue pouring 0.8 mm thick PDMS precursor into the mold, let it stand for 10 min, and vacuum degassing until there is no foam in the PDMS precursor to form a bonding layer. Immerse the barrier layer in the bonding layer and cure it in an oven at 60°C to form a preliminary sample of the bracket.
[0108] Pour silicone oil with a viscosity of 500 cst into a beaker, immerse the PDMS lubricating layer substrate of the initial sample of the bracket in the silicone oil, and after the PDMS lubricating layer substrate has swollen to equilibrium, take out the initial sample of the bracket and let it stand for 1 hour. After wiping off the excess silicone oil on the PDMS lubricating layer substrate, a TPU-PDMS composite bracket is obtained.
[0109] Example 4
[0110] PLA-PTFE composite scaffold (PLA is degradable)
[0111] A PTFE porous membrane with a pore size of 0.45 μm, a porosity of 85%, and a thickness of 200 μm was fixed on a 3D printer sample stage, a PLA filament was loaded into a nozzle of the 3D printer, the bottom plate temperature was adjusted to 60°C, the nozzle temperature was adjusted to 200°C, the height of the sample stage and the printing position of PLA were adjusted so that the printed PLA first porous layer was embedded in the PTFE porous membrane, and the PLA first porous layer with a total thickness of 5.5 mm was continuously printed to obtain a preliminary sample of the scaffold, wherein the pore size in the PLA first porous layer was 200 μm and the porosity was 52%;
[0112] Pour silicone oil with a viscosity of 5000 cst into a beaker, immerse the PTFE lubricating layer substrate of the stent prototype in the silicone oil, and after the PTFE lubricating layer substrate has swollen to equilibrium, take out the stent prototype and let it stand for 55 minutes. Wipe off excess silicone oil on the PTFE lubricating layer substrate to obtain a PLA-PTFE composite stent.
[0113] Example 5
[0114] PVA-PTFE composite scaffold (PVA is degradable)
[0115] A PTFE porous membrane with an upper pore size of 0.45 μm, a lower pore size of 0.22 μm, a porosity of 80%, and a thickness of 200 μm is fixed on the sample stage (i.e., the base plate) of the 3D printer, and the PVA wire is loaded into the nozzle of the 3D printer. The base plate temperature is adjusted to 60°C and the nozzle temperature is adjusted to 200°C. The height of the sample stage and the printing position of the PVA are adjusted, and the PVA is printed on the PTFE so that the first porous layer of the PVA is partially embedded in the PTFE porous membrane. After continuing to print the first porous layer of the PVA with a total thickness of 5.5 mm, a preliminary sample of the bracket is obtained. The pore size in the first porous layer of the PVA is 300 μm, and the porosity is 70%.
[0116] Pour silicone oil with a viscosity of 3000 cst into a beaker, immerse the PTFE lubricating layer substrate of the stent prototype in the silicone oil, and after the PTFE lubricating layer substrate has swollen to equilibrium, take out the stent prototype and let it stand for 38 minutes. Wipe off excess silicone oil on the PTFE lubricating layer substrate to obtain a PVA-PTFE composite stent.
[0117] Example 6
[0118] PLA-PDMS composite scaffold (PLA is degradable)
[0119] PLA was placed on the sample stage of the 3D printer, the base plate temperature was adjusted to 30°C, the nozzle temperature was adjusted to 200°C, and the first porous layer and the barrier layer with a total thickness of 6.5 mm were printed, wherein the thickness of the barrier layer was 0.2 mm, the pore size in the first porous layer was 80 μm, and the porosity was 65%;
[0120] Dow Corning 184A component and Dow Corning 184B component were mixed in a mass ratio of (10:1), stirred evenly to form a PDMS precursor, poured a 1 mm thick PDMS precursor in a mold, left it to stand for 10 min, and vacuum-degassed until there was no foam in the PDMS precursor. The mold and the PDMS precursor were placed in an oven at 80°C for curing for 1 h to obtain a nearly completely cured PDMS lubricating layer substrate;
[0121] Continue to pour 1 mm thick PDMS precursor into the mold, let it stand for 10 minutes, and vacuum degassing until there is no foam in the PDMS precursor to form a bonding layer. Immerse the barrier layer in the bonding layer and cure it in an oven at 50°C to form a PLA-PDMS composite bracket.
[0122] Example 7
[0123] PLA-PTFE composite scaffold (PLA is degradable)
[0124] A PTFE porous membrane with a pore size of 0.45 μm, a porosity of 85%, and a thickness of 200 μm was fixed on the sample stage of the 3D printer, and the PLA filament was loaded into the nozzle of the 3D printer. The base plate temperature was adjusted to 60°C, the nozzle temperature was adjusted to 200°C, and the printing position of PLA was adjusted so that PLA was printed on the PTFE porous membrane to ensure that the first porous layer of PLA printed by the 3D printer could be partially embedded in the pores of the PTFE porous membrane to form a physical fit. The total printing thickness of the first porous layer of PLA was 5.5 mm, the pore size was 200 μm, and the porosity was 52%. After printing, a PLA-PTFE composite scaffold was obtained.
[0125] Test Method
[0126] The stents prepared in Examples 1-7 were used to perform Young's modulus test, compressive strength test, elastic compression strain test, and friction coefficient test. The test results are shown in Table 1.
[0127] Young's modulus test, compressive strength test and elastic compression strain test are all tested in the compression mode of the universal testing machine. You can choose different test modes. The specific test methods are as follows:
[0128] The stent to be tested was cut into a cylinder with a diameter of 10 mm and placed on an Instron universal testing machine for testing under compression mode. The maximum compression load was 950 N and the compression rate was 2 mm / min.
[0129] Friction coefficient test
[0130] The lubricating layer of the bracket to be tested was prepared into a 76*26*1mm cuboid and placed on an Anton Paar friction and wear testing machine for testing. The grinding pair was a 6.35mm ceramic ball and the friction load was 10N. The lubricating layer of the bracket to be tested was directly rubbed against the grinding pair. The single reciprocating stroke of the bracket to be tested was 6mm, the reciprocating frequency was 2Hz, and the single experimental time was 25min.
[0131] Table 1
[0132]
[0133] The test results show that the cartilage repair scaffold has good structural stability, a low friction coefficient and good lubrication.
[0134] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A scaffold for cartilage repair, characterized in that: include: The lubricating layer (1) is made of a non-degradable material and has a lubricating effect; The surface layer (3) comprises a porous layer having a porous structure, and the surface layer (3) is made of a biodegradable material having physical compatibility; or the surface layer (3) is made of a non-degradable material having biological stability; a bonding layer (2) connected between the lubricating layer (1) and the porous layer, so that the lubricating layer (1) forms a fastening structure with the porous layer through the bonding layer (2); The surface layer (3) further comprises a barrier layer (33), the porous layer comprises a first porous layer (31), and the barrier layer (33) is connected between the first porous layer (31) and the bonding layer (2) to isolate the first porous layer (31) and the bonding layer (2); The porous layer further comprises a second porous layer (32), wherein the second porous layer (32) is connected between the barrier layer (33) and the bonding layer (2); The ratios of the thickness of the surface layer (3), the thickness of the bonding layer (2) and the thickness of the lubricating layer (1) to the total thickness of the stent are 60%-80%, 0.1%-10% and 1%-35%, respectively.
2. The cartilage repair scaffold according to claim 1, characterized in that: The friction coefficient of the non-degradable material used to prepare the lubricating layer is 0.05-1.
3. The cartilage repair scaffold according to claim 2, characterized in that: The friction coefficient of the non-degradable material used to prepare the lubricating layer is 0.05-0.
3.
4. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The lubricating layer (1) is made of the following materials: one or more of polymer oil gel or porous materials containing lubricating liquid.
5. The cartilage repair scaffold according to claim 4, characterized in that: The porous material containing the lubricating liquid has a pore size of 0.1-1 μm, a porosity of 25%-95%, and a mass fraction of the lubricating liquid in the porous material of 20%-80%.
6. The cartilage repair scaffold according to claim 5, characterized in that: The viscosity of the lubricating liquid is 5-10000 cst.
7. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The surface layer is made of 3D printable biomedical polymer material.
8. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The pore diameter of the porous layer is 10-500 μm.
9. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The porosity of the porous layer made of degradable material is 20%-90%, and the porosity of the porous layer made of non-degradable material is not less than 90%.
10. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The porous structure is a regular through hole with uniform size; or, the porous structure is a sponge structure.
11. The cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The bonding layer (2) is made of the following materials: one or more of a polymer oil gel, a porous material containing a lubricating liquid, a 3D printable biomedical polymer material or a bioadhesive.
12. The cartilage repair scaffold according to claim 11, characterized in that: The polymer oil gel is polydimethylsiloxane oil gel; The porous material containing lubricating liquid is a polytetrafluoroethylene porous membrane containing perfluorinated lubricating oil; The 3D printable biomedical polymer material is one or more of polylactic acid, polycaprolactone, polyvinyl alcohol or thermoplastic polyurethane; The biological adhesive is α-butyl cyanoacrylate.
13. A method for preparing the scaffold for cartilage repair according to any one of claims 1 to 12, characterized in that: The steps include: Forming a biocompatible degradable material into a porous layer by 3D printing; or forming a biostable non-degradable material into a porous layer by 3D printing; A non-degradable material having a lubricating effect is made into a lubricating layer (1); The bonding layer (2) is arranged between the porous layer and the lubricating layer (1) to form a bracket.
14. A method for preparing a cartilage repair scaffold according to any one of claims 2 to 12, characterized in that: The steps include: The biocompatible degradable material is formed into a porous layer and a barrier layer (33) by 3D printing; or the biostable non-degradable material is formed into a porous layer and a barrier layer (33) by 3D printing; The non-degradable material having lubricating effect is made into a lubricating layer substrate; The bonding layer (2) is arranged between the barrier layer (33) and the lubricating layer substrate to form a preliminary sample of a bracket, and the lubricating layer substrate is then subjected to a lubricity treatment and then formed into a bracket.
15. The method for preparing a cartilage repair scaffold according to claim 14, characterized in that: The method for treating the lubricity of the lubricating layer substrate comprises: Swelling lubricating liquid: placing the lubricating layer substrate in the lubricating liquid to swell the lubricating layer substrate to swelling equilibrium; or, Pouring lubricating liquid: Pouring lubricating liquid into the lubricating layer substrate and letting it stand.
16. The method for preparing a scaffold for cartilage repair according to claim 14, characterized in that: The 3D printing method includes: one or more of a fused deposition method, a selective laser sintering method or a laser photocuring method.
17. The method for preparing a cartilage repair scaffold according to claim 14, characterized in that: The preparation method of the bonding layer (2) comprises: forming the bonding layer (2) by physically interlocking the surface layer (3) and the lubricating layer (1) or the lubricating layer substrate; or bonding and curing the surface layer (3) and the lubricating layer (1) or the lubricating layer substrate with a bioadhesive to form the bonding layer (2).
18. The method for preparing a scaffold for cartilage repair according to claim 14, characterized in that: The method also includes performing surface pretreatment on the materials for preparing the lubricating layer (1), the bonding layer (2) and the surface layer (3).
Citation Information
Patent Citations
Bionic oriented cartilage scaffold released by two-factor program and preparation method of bionic oriented cartilage scaffold
CN108159496A
Bone and cartilage integrated repair support and preparation method thereof
CN108992212A
Articular cartilage repair
US20180021138A1